Competition policy convergence: where next? - Frederic Michael Scherer (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1996)
As the 20th Century dawned, there were radical divergences in the policies individual nations pursued toward restraints of competition by cartels and monopolies. Since World War II there has been considerable convergence as an increasing large number of nations have adopted explicit pro-competition policies. This paper traces the reasons for the divergence and then convergence and asks what important steps remain to be taken, especially where the concerns of international trade policy and competition policy intersect. A proposed augmentation of the World Trade Organization's functions to deal with competition policy issues is examined.
Keywords: 330